1992
DOI: 10.21273/jashs.117.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Tomatoes at Mature-green and Breaker Ripeness Stages to Internal Bruising

Abstract: Internal bruising (IB) caused by handling impacts results in disruption of normal ripening in tomato (Lycopersicon esculentum Mill.) locular gel. It was selected as an injury indicator to investigate the effect of drop height (O, 10, 20, 30 cm) onto an unpadded surface and number of impacts (one or two) for three tomato cultivars. For mature-green (MG) tomatoes, significant incidence of IB (5% to 45%) was found in all cultivars for single drops on opposite sides of fruits fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
14

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 6 publications
1
12
0
14
Order By: Relevance
“…According to our data, locule tissue ripening was markedly affected by physical impact. This result is in line with the work of Halsey (1955), McColloch (1962, Sargent et al (1992), and Moretti et al (1998). Locule tissue components are more fluid and more readily perceived by taste receptors, and therefore a greater contribution to tomato flavor than other tissues (Stevens et al, 1977).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…According to our data, locule tissue ripening was markedly affected by physical impact. This result is in line with the work of Halsey (1955), McColloch (1962, Sargent et al (1992), and Moretti et al (1998). Locule tissue components are more fluid and more readily perceived by taste receptors, and therefore a greater contribution to tomato flavor than other tissues (Stevens et al, 1977).…”
Section: Resultssupporting
confidence: 84%
“…Hatton and Reeder (1963) described tomato fruit with internal bruising as having a disorganized, collapsed, and cloudy locule tissue. Sargent et al (1992) observed that tomato fruit at the breaker stage were more susceptible to internal bruising than fruit at the mature-green stage. MacLeod et al (1976) observed that ethylene and CO 2 evolution increased with the number of impacts.…”
Section: Methodsmentioning
confidence: 94%
“…Fruit are sorted for color, size, grade, and defects, before eventual packaging. However, fruit are easily bruised during transfer from field bins to a grading line (Sargent, Brecht, & Zoellner, 1992). To avoid injury to fruit, most tomato packinghouses utilize a wet-dump system, where fruit are bulk transferred to a large tank (dump tank) of re-circulating water and then moved to a packing line by a flume of water (current of water moving continuously from beginning of dump tank to mechanical elevators).…”
Section: Postharvest Handlingmentioning
confidence: 99%
“…Quanto ao estádio de maturidade, foram selecionados frutos apresentando de 1% a 60% de coloração vermelha e então colocados nas embalagens estudadas (conforme especificadas nas Tabelas 1 e 2 e Figura 1), enquanto que alguns permaneceram em 3 caixas K para fins de comparação. Vinte frutos foram colocados em bandejas de papelão com separação individual para evitar qualquer vibração, impacto ou compressão mecânica durante seu transporte, constituindo o grupo controle segundo SINGH, SINGH, BATHEJA [13], SARGENT, BRECHT, ZOELLNER [12]. As embalagens foram dis-postas, aleatoriamente, no veículo (caminhonete F 1000), mas procurando submetê-las às mesmas condições de transporte, quanto à carga a ser suportada, exposição à radiação solar/umidade e posição em relação à roda (fator que pode influenciar nos impactos de vibração).…”
Section: -Matéria-primaunclassified
“…De acordo com SARGENT, BRECHT, ZOELLNER [12], os tomates transportados a longas distâncias estão, freqüentemente, sob condições que podem promover o crescimento de organismos deteriorantes nos locais de injúrias mecânicas (como ferimentos por impacto e compressão, cortes e abrasões). Sendo as injúrias mecânicas cumulativas, as várias etapas do manuseio, do campo ao consumidor, devem ser cuidadosamente coordenados e integrados para minimizar as perdas na qualidade do produto.…”
Section: -Introduçãounclassified